Holocynips illinoiensis, sp. nov., a new species of oak gall wasp (Hymenoptera: Cynipidae) from the USA - Nicholls, James A.; Furlan, Nick E.; Melika, George (Zootaxa, 2023)
A new species, Holocynips illinoiensis Melika & Nicholls, sp. nov. is described from the Nearctic (America north of Mexico). Description, diagnoses, information on biology and host association is given for the new species, as well as preliminary discussion on the coherence of the genus Holocynips.